Pengenalan Perbanyakan Bibit Tanaman Buah Secara Vegetatif Kepada Masyarakat Desa Tabalagan - Edi, Syahrial; Fariadi, Herri (Jurnal Kewirausahaan dan Bisnis, 2024)
This Thematic Real Work Lecture (KKN) Work Program in Universitas Dehasen Bengkulu 2023 was held at the Department of Food Crops Horticulture and Plantations UPTD BITPHPP in Tabalagan Village, Semidang Lagan District, Central Bengkulu Regency, Bengkulu Province. The work program carried out during this KKN period is "Introduction of Vegetative Propagation of Fruit Plant Seedlings to the Tabalagan Village Community ". This work program aims to make the community aware of how to propagate fruit plants effectively and efficiently. So that the output that you want to produce from this activity is a scientific article in the Journal of Community Service, a video of activities published on GoogleDrive and a Final Report in the form of a Report on the Results of the Implementation of UNIVED Bengkulu Thematic KKN Period 1. The methods used in Thematic KKN are participation, observation, interview, literature study and documentation.